2017
DOI: 10.1021/acs.jmedchem.7b01009
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Acyclovir Derivatives as Potential Antiviral Agents: Design, Synthesis, and Biological Evaluation of New Acyclic Nucleoside ProTides

Abstract: Following our findings on the anti-HIV activity of acyclovir phosphate prodrugs, we herein report the ProTide approach applied to a series of acyclic nucleosides aimed at the identification of novel and selective antiviral (i.e. HIV) agents. Acyclic nucleoside analogues used in this study were identified through a virtual screening using adenylate/guanylate kinase, HIV RT, and human DNA polymerase. A total of thirty-nine new phosphate prodrugs were synthesised and evaluated against HIV-1 (in in vitro and in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…While virtual screening of compounds that are active against mutant RT forms is not widely used, an application of molecular docking to virtual screening of compounds, active against wild-type of RT can be performed [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Typically such studies provide some insights into intermolecular interactions affecting both wild-type and mutant enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…While virtual screening of compounds that are active against mutant RT forms is not widely used, an application of molecular docking to virtual screening of compounds, active against wild-type of RT can be performed [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. Typically such studies provide some insights into intermolecular interactions affecting both wild-type and mutant enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the cytotoxicity observed with these prodrugs, very recently a virtual screening on a library of ACV derivatives was reported. 168 Docking experiments with a database of 3600 compounds against three different enzymes encompassing HIV reverse transcriptase, adenylate or guanylate kinase, and a model of DNA polymerase γ resulted in the selection of five NAs as potentially strong RT inhibitors and weak cellular DNA polymerase inhibitors including GCV, PCV, 6-Cl-PCV, 6-OMe-PCV and 2′-SH-GCV. Several phosphoramidate prodrugs of the selected NAs were synthesized and assessed for their potency against HIV, HSV, VZV, and HCMV.…”
Section: Protide Approach Application To Antiviral Nucleosidesmentioning
confidence: 99%
“…As reported before, over the last 20 years, ANPs have emerged as a novel class of clinically effective antiviral agents. 168 Explorations of various types of nucleoside phosphonate prodrugs have also led to the design and development of their aryloxyamidate prodrugs. ProTides originally designed to deliver nucleoside monophosphates, have also been successfully applied to nucleoside phosphonates.…”
Section: Protide Approach Application To Antiviral Nucleosidesmentioning
confidence: 99%
“…7 Many studies have shown that purine derivatives adjacent to heteroatoms have potential drug activity, such as 9-(tetrahydrofuryl)adenine (9-THF-Ade), A 3 adenosine receptor antagonist, and antiviral active molecule (Scheme 1b). 8…”
Section: Introductionmentioning
confidence: 99%